Understanding household preferences on the production, consumption, and sale of nutritious crops - Aberman, Noora-Lisa; Roopnaraine, Terry (International Food Policy Research Institute, 2018)
Value chains and agricultural commercialization are increasingly promoted as mechanisms for agricultural transformation, inclusive growth, and, more recently, improved food security and diets. In particular, donors and implementers of nutrition and food security programs are promoting the production of nutritious crops as a mechanism for improving the quality of and diversity in the diets of the rural poor. However, while a theoretical basis exists for suggesting that production of these crops may improve diets, there is limited empirical understanding of how agricultural production impacts diets (impact pathways) and under what circumstances production of nutritious foods can lead to improved diets. This chapter examines pathways from production to diets by analyzing qualitative data collected from three districts in three regions of Malawi. The analysis specifically explores contemporary food preferences, patterns, and decisions related to crop sales, and gendered household decision-making dynamics. The results indicate that households desire diverse diets, but access to (affordability) and availability of diverse foods are limiting factors, as is a dominant maize-first approach to assuring household food security. In addition, many nutritious crops that households produce are both consumed and sold. Decisions about what or how much to sell are based on consideration of a range of factors. Nutrition training—promoting consumer demand for key commodities—combined with value chain approaches to decrease price and increase availability might successfully improve diets in this context.